2023
DOI: 10.1038/s41597-023-02618-w
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological model-based streamflow reconstruction for Indian sub-continental river basins, 1951–2021

Dipesh Singh Chuphal,
Vimal Mishra

Abstract: Streamflow is a vital component of the global water cycle. Long-term streamflow observations are required for water resources planning and management, hydroclimatic extremes analysis, and ecological assessment. However, long-term streamflow observations for the Indian-Subcontinental (ISC) river basins are lacking. Using meteorological observations, state-of-the-art hydrological model, and river routing model, we developed hydrological model-simulated monthly streamflow from 1951–2021 for the ISC river basins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…The Central Water Commission (CWC, Government of India) monitors and provides daily streamflow and reservoir storage for Indian river basins through the India‐WRIS platform. Previous studies used streamflow and reservoir storage data from India‐WRIS to examine the climate change impact on water availability in India (Asoka & Mishra, 2020; Chuphal & Mishra, 2023a; Mishra, 2020; Tiwari & Mishra, 2022). We selected 36 dams (height ≥100 m and capacity ≥1 km 3 ) from the National Register of Large Dams (NRLD) (Figure 1) based on the availability of observed streamflow and reservoir storage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Central Water Commission (CWC, Government of India) monitors and provides daily streamflow and reservoir storage for Indian river basins through the India‐WRIS platform. Previous studies used streamflow and reservoir storage data from India‐WRIS to examine the climate change impact on water availability in India (Asoka & Mishra, 2020; Chuphal & Mishra, 2023a; Mishra, 2020; Tiwari & Mishra, 2022). We selected 36 dams (height ≥100 m and capacity ≥1 km 3 ) from the National Register of Large Dams (NRLD) (Figure 1) based on the availability of observed streamflow and reservoir storage.…”
Section: Methodsmentioning
confidence: 99%
“…As streamflow and reservoir storage observations in the Indian subcontinental river basins are limited, simulations from the hydrological models can fill this critical gap (Asoka & Mishra, 2020; Chuphal & Mishra, 2023a; Tiwari & Mishra, 2019; Vegad & Mishra, 2022). Mahto and Mishra (2020) reported that India faces frequent flash droughts during the summer monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…The metrological data of the "disturbed period" were used to calibrate the model to reconstruct the natural streamflow. During the disturbed period, the simulated streamflow is considered to be the natural streamflow, which is affected only by climatic factors (Chuphal & Mishra, 2023).…”
Section: Reconstruction Of a Natural Streamflow By Using Swat Modelmentioning
confidence: 99%
“…Surveys have indicated a direct link between climate change's impact on water resources and shifts in the water cycle [5][6][7]. Increasing temperatures notably affect river flows through changes in rainfall patterns [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding and mapping the water cycle's changes in detail is crucial for combating climate change and sustainably managing water resources. Additionally, Water 2024, 16, 1422 2 of 24 monitoring and analyzing the variability in hydrological variables (precipitation, evapotranspiration, and streamflow) are essential for assessing the impacts of climate change and to ensure the sustainable use of water resources [6,13]. Analysis of the trends of river flow is essential for effective water resource management and sustainability [14,15].…”
Section: Introductionmentioning
confidence: 99%